The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/pc.26165
|View full text |Cite
|
Sign up to set email alerts
|

Surface wettability, tensile mechanical performance, and tribological behavior of polyimide/polytetrafluoroethylene blends enhanced with hydroxylated multiwalled carbon nanotubes at high relative humidity

Abstract: Multiwalled carbon nanotubes were hydroxylated (MWCNTs-OH) by a strong acid mixture and then used as a reinforcement nanofiller in blends of polytetrafluoroethylene (PTFE) and polyimide (PI) to fabricate MWCNTs-OH/ PTFE/PI nanocomposites. The influences of MWCNTs-OH additions on the surface wettability, tensile mechanical property, and tribological behaviors of MWCNTs-OH/PTFE/PI nanocomposites under different relative humidity were investigated. Test results indicate that the introduction of MWCNTs-OHcan drama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Liu and co-workers also reported that the filled MWCNT in ultra-high molecular weight polyethylene (UHMWPE) composite exhibited high wear resistance and low friction coefficient compared to pure UHMWPE [ 47 ]. According to Yan and Xue, incorporating carbon nanotubes into a polymer matrix improves the composite’s tensile and tribological properties [ 48 ]. An enhancement in wear resistance is evident after adding the hybrid fillers (HYB and PHY composite).…”
Section: Resultsmentioning
confidence: 99%
“…Liu and co-workers also reported that the filled MWCNT in ultra-high molecular weight polyethylene (UHMWPE) composite exhibited high wear resistance and low friction coefficient compared to pure UHMWPE [ 47 ]. According to Yan and Xue, incorporating carbon nanotubes into a polymer matrix improves the composite’s tensile and tribological properties [ 48 ]. An enhancement in wear resistance is evident after adding the hybrid fillers (HYB and PHY composite).…”
Section: Resultsmentioning
confidence: 99%
“…The friction coefficient curves of EG/PES/PI composites at different evaluated temperatures were collected via the data acquisition system of Anton Paar's Standard Pin-on-Disk Tribometer and the average friction coefficients were calculated from the frictional data of these composites at stable wear stages. The wear rates of EG/PES/PI composites could be computed according to the following Equations: 26,27…”
Section: Tribological Experimentsmentioning
confidence: 99%
“…Polyimide (PI) resin matrix composites which have excellent electrical, thermal and mechanical stability have gained important applications in aviation equipment, such as wings and airframes of military aircraft, reverser stang fairings, ultra-high-speed fan blades. [1][2][3] After years of work by researchers, [4][5][6][7][8][9][10] composites prepared from PI resin have formed a multilevel material system with temperature resistance ranging from low to high. Currently, the most widely used thermosetting PIs include nadic anhydride-terminated PIs, nitrile-terminated PIs and phenylethynyl-terminated PIs.…”
Section: Introductionmentioning
confidence: 99%